An Overview about the Influenza a Virus - Neyazi, Ghulam Rabani; Mukhlis , Hujatullah; Mohammadi, Mohammad Hamid (Journal for Research in Applied Sciences and Biotechnology, 2024)
As influenza A can cause pandemics and epidemics with high rates of morbidity and mortality, it continues to be a major worldwide health concern. It is critical to comprehend its development, implications, and upcoming difficulties. This review explores the historical background, molecular causes, and modern management approaches for influenza A. Influenza A presents difficulties due to its rapid mutation rates and capacity to infect a wide variety of hosts. Even if vaccination is the main preventive measure, existing tactics have drawbacks that call for the creation of novel solutions. The overview covers the molecular mechanisms underpinning influenza A's pathogenicity, as well as the virus's historical history and effects on human health. It also looks at modern methods of treating influenza A, such as antiviral medication and immunization. To lessen the threat posed by influenza A, the review looks ahead, highlighting future research challenges and initiatives. It emphasizes the significance of enhancing global surveillance efforts, developing novel treatment options, and improving vaccine responses.